2020
DOI: 10.3390/microorganisms8050620
|View full text |Cite
|
Sign up to set email alerts
|

Antibiofilm Activity of a Trichoderma Metabolite against Xanthomonas campestris pv. campestris, Alone and in Association with a Phage

Abstract: Biofilm protects bacteria against the host’s immune system and adverse environmental conditions. Several studies highlight the efficacy of lytic phages in the prevention and eradication of bacterial biofilms. In this study, the lytic activity of Xccφ1 (Xanthomonas campestris pv. campestris-specific phage) was evaluated in combination with 6-pentyl-α-pyrone (a secondary metabolite produced by Trichoderma atroviride P1) and the mineral hydroxyapatite. Then, the antibiofilm activity of this interaction, called a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Our study suggests that phages complexed with lactoferrin are a powerful biological tool, able to specifically kill Hp without toxic effect on the host cells [41], thus representing a good therapeutic strategy in Hp infection. Moreover, the use of hydroxyapatite as carrier, able to improve the biological properties of both Hp ϕ and LF [21,33], further supports our data. The efficacy of the above-described treatments was tested by using an in vitro model of Hp infection.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our study suggests that phages complexed with lactoferrin are a powerful biological tool, able to specifically kill Hp without toxic effect on the host cells [41], thus representing a good therapeutic strategy in Hp infection. Moreover, the use of hydroxyapatite as carrier, able to improve the biological properties of both Hp ϕ and LF [21,33], further supports our data. The efficacy of the above-described treatments was tested by using an in vitro model of Hp infection.…”
Section: Discussionsupporting
confidence: 86%
“…Total RNA was extracted following the Tryzol reagent protocol (Invitrogen, Thermo Fisher Scientific, Waltham, MA, USA). Gene transcript levels were measured using Power SYBR ® Green PCR Master Mix (Applied Biosystems ® , Thermo Fisher Scientific, Waltham, MA, USA) on a QuantStudio™ 3 Real-Time PCR System (Applied Biosystems ® , Thermo Fisher Scientific, Waltham, MA, USA) [33]. QuantStudio Design & Analysis Sofware v1.1 (Applied Biosystems Thermo Fisher Scientific, Waltham, MA, USA) was used for the analysis of gene expression.…”
Section: Quantitative Gene Expression Analysismentioning
confidence: 99%
“…Recent advances in biofilm eradication also involve the intervention of lytic phages. In the study of Papaianni et al (2020) [15] the lytic activity of Xccϕ1 (Xanthomonas campestris pv. campestris-specific phage) was evaluated in combination with 6pentyl-α-pyrone (a secondary metabolite produced by Trichoderma atroviride P1) associated with hydroxyapatite.…”
Section: Increasing Knowledge On Bioactive Propertiesmentioning
confidence: 99%
“…The water extracts of Ocimum gratissimum and Tylophora asthmatica were effective in inhibiting the growth of Xcc , while the alcohol extract of O. gratissimum was the most effective in inhibiting the growth of Xcc , followed by that of Calotropis gigentea , T. asthmatica , Ocimum sanctum , Nigella sativa , and Ruta graveolens ( Kumar et al, 2018 ). In addition, the Trichoderma atroviride metabolite, 6-pentyl-α-pyrone, also could inhibit Xcc by increasing the antibiofilm activity ( Papaianni et al, 2020 ). Most of these studies only analyzed the antibacterial activity of the total extracts from the whole plant or some organs and did not study the components related to BR resistance ( Table 1 ).…”
Section: Biological Control Of Xanthomonas Campestris ...mentioning
confidence: 99%
“…Potentially, weakly virulent Xcc could be deployed to activate defense mechanisms and increase the persistence of bacteriophages specific to the target Xcc on Brassica campestris , B. nigra , Brassica geniculata , and R. sativus leaf surfaces ( Schaad and Ignatov, 2019 ). A study on the anti- Xcc mechanism showed that the Xcc -specific bacteriophage Xcc φ1 could inhibit Xcc by interfering with the genes ( rpf , gumB , clp , and manA ) involved in the formation of biofilms ( Papaianni et al, 2020 )…”
Section: Biological Control Of Xanthomonas Campestris ...mentioning
confidence: 99%